Perfluorooctanoic acid induces abnormal heart development via aryl hydrocarbon receptor-mediated oxidative stress and apoptosis in zebrafish larvae - Xueyi CHEN; Tianchi MA; Kang WANG; Tao CHEN; Yan JIANG (环境与职业医学)
BackgroundIn recent years, a growing number of studies have indicated that perfluorooctanoic acid (PFOA) exposure can impact heart development, though the specific mechanisms remain elusive. The aryl hydrocarbon receptor (AHR) is a critical environmental sensor capable of inducing oxidative stress and cell apoptosis. ObjectiveTo explore the role of AHR in the cardiac developmental toxicity of PFOA by using zebrafish embryo as an in vivo model. MethodsZebrafish embryos at 2 h post-fertilization (2 hpf) were exposed to dimethyl sulfoxide (DMSO) control, 1, 10, 100, and 1000 μg·L−1 of PFOA. The AHR inhibitor CH223191 (CH) was added to the high-concentration group (1000 μg·L−1) to form an intervention group. Under a dissecting microscope, the survival rate, mortality rate, heart rate, and heart malformation rate of 72 hpf zebrafish larvae were assessed. The activity of AHR was measured using 7-ethoxyresorufin-O-dealkylation (EROD) staining. The levels of intracellular and mitochondrial ROS in the heart of zebrafish larvae were assessed using dichloro-dihydro-fluorescein diacetate and MitoSOX™ Red, respectively. Apoptosis was examined using acridine orange (AO) staining and Immunofluorescence method. Total RNA was extracted from dissected hearts, and mRNA expression levels of oxidative stress-related genes (sod2, cat) and apoptosis-related gene (p53) were analyzed using quantitative PCR. ResultsCompared to the DMSO control group, PFOA at even the lowest concentration (1 μg·L−1) increased heart malformation rate (P＜0.05) and reduced heart rate (P＜0.01) in the zebrafish larvae at 72 hpf, and the results showed a clear concentration-response relationship. Adding the AHR inhibitor CH significantly decreased heart malformation rate and restored heart rate to the control group level. The EROD results showed that PFOA at 1000 μg·L−1 increased AHR activity (P＜0.001). Further studies revealed that PFOA caused a dose-dependent increase in intracellular ROS (P<0.001) and an increase in mitochondrial ROS (P<0.001) in the heart region of zebrafish larvae. A high dose of PFOA (1000 μg·L−1) also induced elevated mRNA expression levels of oxidative stress-related genes sod2 and cat (P<0.05). Addition of the AHR inhibitor CH effectively antagonized PFOA-induced (1000 μg·L−1) oxidative stress in the heart of zebrafish larvae (P<0.001). In addition, PFOA exposure induced a concentration-dependent increase in apoptotic bodies in the heart of zebrafish larvae (P<0.05). Moreover, PFOA at 1000 μg·L−1 caused an increase in the cleaved-caspase 3 immunofluorescence signal (P<0.05) as well as overexpression of the apoptosis-associated gene p53 (P<0.001).which were attenuated by the CH supplementation. ConclusionPFOA triggers oxidative stress and apoptosis via AHR activation in the heart of zebrafish larvae, resulting in cardiac defects.